Chapter Natural resources and coastal productive settlements in southern Puglia - Tartara, Patrizia (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The systematic topographic researches conducted for many years by the CNR and by the Ancient Topography Laboratory of the University of Salento, in particular in the Salento peninsula, brought to an exponential increase in the knowledge of archaeological evidences and consequently to the analysis and reconstruction of the evolution of human settlement in the territory in the different phases. Data collected with detailed survey and use of various traditional and advanced technologies are collected in the "Territorial Information System of Cultural Heritage of the Italian territory" of the CNR